Negotiating Afropolitanism : essays on borders and spaces in contemporary African literature and folklore - Wawrzinek, Jennifer; Makokha, J. K. S. (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2011)
Negotiating Afropolitanism brings together scholars in African studies from across the world in order to critically examine the representations, transgressions, disruptions, and/or redrawings of borders and spaces in contemporary African literature, culture and folklore. The essays collected here offer innovative and fresh critical perspectives on postcolonial themes within contemporary Africa. Individually they investigate such themes as identity, diaspora, hybridity, translation, the space between, textual frontiers, translocation and multilocalities, migration, nomadology, polylingualism, and multiculturalism. Together they map the rich terrain of culture, literature and folklore in contemporary Africa, from the works of writers such as Idris Chraibi, Wole Soyinka, Ben Okri, E.B. Dongala, Calixthe Beyala, Patrice Nganang, Nuruddin Farah and Abdulrazak Gurnah, to those of Pepetela, Goretti Kyomuhendo, Jamal Mahjoub, Yusuf Dawood, M.G. Vassanji, and J.M. Coetzee, as well as Afrophone oral artists and radio performers. This volume will be of interest to anyone with an interest in African studies, postcolonialism, cultural and literary studies.